Analyzing the reason for students' lack of interest in learning arts and culture as subjects in Class IV C at SDN 210 Babakan Sinyar - Nasihah, Farah Lutfiah; Istiqomah, Riski Alita; Wiyanto, Yuli Tri (Journal of Education Method and Learning Strategy, 2024)
The study entitled "Analysis of the Influence of Students' Lack of Interest in Cultural Arts Subjects in Class IV C at SDN 210 Babakan Sinyar Kota Bandung" aims to analyze the factors that influence the lack of interest in learning among students of class IV C at SDN 210 Babakan Sinyar in the cultural arts subject. The subjects of this study were 25 students of class IV C, consisting of 15 females and 10 males. The research methods used in data collection were interviews, observations, and documentation. The data analysis technique in this study was descriptive qualitative using purposive sampling technique through interviews with 1 homeroom teacher and the distribution of questionnaires to students of class IV C as the data collection method. The theory used in this study was the learning environment theory (Nurdiana, 2023). The results of this study indicate that students' interest in the cultural arts subject is influenced by four factors: (1) the quality of cultural arts learning, (2) learning facilities, (3) intrinsic and extrinsic motivation, and (4) social support.